2013
DOI: 10.1186/1471-2202-14-103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simultaneously performed cognitive and physical training in older adults

Abstract: BackgroundWhile many studies confirm the positive effect of cognitive and physical training on cognitive performance of older adults, only little is known about the effects of simultaneously performed cognitive and physical training. In the current study, older adults simultaneously performed a verbal working memory and a cardiovascular training to improve cognitive and motor-cognitive dual task performance. Twenty training sessions of 30 minutes each were conducted over a period of ten weeks, with a test sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(181 citation statements)
references
References 63 publications
(75 reference statements)
6
165
0
10
Order By: Relevance
“…Sin embargo, no está claro qué tipo de intervención presenta mejores resultados, si el entrenamiento aeróbico, el de fuerza, el de flexibilidad o la combinación entre entrenamiento de las funciones cognitivas y de actividad física (23).…”
Section: Discussionunclassified
“…Sin embargo, no está claro qué tipo de intervención presenta mejores resultados, si el entrenamiento aeróbico, el de fuerza, el de flexibilidad o la combinación entre entrenamiento de las funciones cognitivas y de actividad física (23).…”
Section: Discussionunclassified
“…For example, Theill et al (2013) paired a verbal working memory task with concurrent moderate-intensity aerobic exercise. Both the multimodal and pure cognitive training groups showed the same degree of cognitive improvement with the exception of a task of visual memory, which improved more in the multimodal group.…”
Section: Multimodal Approaches: Combining Cognitive and Aerobic Trainingmentioning
confidence: 99%
“…Although activities related to dementia prevention have hitherto mostly consisted of exercises that only target motor functions, it has been reported that greater dementia preventive effects can be achieved by performing simultaneous cognitive function and motor function exercises [4]. Recently, exercises have been developed in which cognitive function and motor function exercises are performed simultaneously.…”
Section: Exercises To Prevent Dementiamentioning
confidence: 99%
“…Effective ways of preventing dementia are thought to include lifestyle and dietary improvements, social activity, and appropriate exercise [2], [3]. Also, methods that combine motor function and cognitive function exercises have been reported to be highly effective [4]. Antagonistic exercises aim to prevent dementia by having people perform different movements with the upper and lower limbs on the left and right sides as a way of exercising motor function and cognitive function simultaneously [5], [6].…”
Section: Introductionmentioning
confidence: 99%